2008
DOI: 10.1162/jocn.2008.20504
|View full text |Cite
|
Sign up to set email alerts
|

Learning through Hand- or Typewriting Influences Visual Recognition of New Graphic Shapes: Behavioral and Functional Imaging Evidence

Abstract: Fast and accurate visual recognition of single characters is crucial for efficient reading. We explored the possible contribution of writing memory to character recognition processes. We evaluated the ability of adults to discriminate new characters from their mirror images after being taught how to produce the characters either by traditional pen-and-paper writing or with a computer keyboard. After training, we found stronger and longer lasting (several weeks) facilitation in recognizing the orientation of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
212
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 68 publications
16
212
2
4
Order By: Relevance
“…One may speculate that at the beginning of learning to read, the dorsal system probably has an important role in disambiguating the orientation of alphabetic symbols, but after substantial exposure to them in a fixed orientation, the dorsal system is no longer necessary to this task, as the ventral system encodes the orientation of letters. Such a dorsal-to-ventral shift underlying the sensitivity to letter orientation would be consistent with the view that, in the initial stage of learning to read, left-right discrimination of letters is primarily guided by motor representations of handwriting acts encoded in parietal and motor/premotor areas (Longcamp et al, 2008). This hypothesis, however, remains to be directly tested.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…One may speculate that at the beginning of learning to read, the dorsal system probably has an important role in disambiguating the orientation of alphabetic symbols, but after substantial exposure to them in a fixed orientation, the dorsal system is no longer necessary to this task, as the ventral system encodes the orientation of letters. Such a dorsal-to-ventral shift underlying the sensitivity to letter orientation would be consistent with the view that, in the initial stage of learning to read, left-right discrimination of letters is primarily guided by motor representations of handwriting acts encoded in parietal and motor/premotor areas (Longcamp et al, 2008). This hypothesis, however, remains to be directly tested.…”
Section: Discussionsupporting
confidence: 77%
“…Longcamp et al (2008) suggest that a movement code for handwriting gestures, particularly involving the bilateral inferior parietal lobule, may help in disambiguating symmetrical letters. Once reading expertise sets in, the recognition of letters in a fixed orientation (mirror discrimination) becomes automatic and effortless.…”
Section: Discussionmentioning
confidence: 99%
“…This proposal is supported by evidence showing that the motor processes associated with writing reinforce a child's ability to recognize alphanumerical symbols [6]. Longcamp et al [7] have demonstrated the importance of learning the motor representations of symbols for later visual recognition in adults. They taught participants new characters taken from the Gujarati or Bengali alphabets: half were trained using a typewriter and half by copying the characters by hand.…”
Section: Introductionmentioning
confidence: 94%
“…This cannot be achieved unless one continues training to write swiftly. This is supported by the neuro-scientific study of Longcamp et al (2008) which evaluates the ability of adults' recognition after being trained to recognize new characters using either handwriting with pen and paper or typing with computer keyboard. Results have revealed that recognizing the written characters with pen and paper have lasted in memory more than the typed ones.…”
Section: Handwriting Memory Activating and Information Recallingmentioning
confidence: 99%